The Role of Circuit Training in Badminton: A Systematic Literature Review - Wahyu Eko Widiyanto; Soegiyanto KS; M. Furqon Hidayatullah; Donny Wira Yudha Kusuma (International Conference on Science, Education, and Technology, 2023)
Badminton is a sport that demands constant and quick movement. Physical condition is a fundamental ability to support a player's movement. Appropriate and precise training is the key to develop a player's physical abilities. Circuit training is believed to provide innovative training methods to improve the physical condition of badminton players. This study aims to determine the role of circuit training in the physical condition of a badminton player. This study is a literature review. Data collection for the literature review is done using a database search tool as a source of literature. The search engine used to determine articles is Google Scholar, Eric, and Science Direct, covering a period of 5 years from 2019 to 2023. The collection of literature data is conducted using the PRISMA method. Based on the analysis results, circuit training serves as an innovative approach to enhancing physical fitness. Competitive and continuous training is likely to result in an effective, efficient and attractive form of training.